Awareness, Acceptability, and Perceived Effectiveness of Text-Based Therapy Among Graduate Students: Cross-sectional Study - Samari A Blair; Andrea N Brockmann; Kelsey M Arroyo; Chelsea A Carpenter; Kathryn M Ross (JMIR Publications, 2022)
BackgroundResearch has suggested that there is a mental health crisis occurring among graduate students in the United States. Moreover, many students go without effective treatment owing to the limited availability of mental and behavioral health resources on college campuses. Text-based therapy may represent a viable method for increasing access to mental health support for graduate students, but little is known regarding its acceptability in this population. ObjectiveThe purpose of this study was to assess how graduate students perceive text-based therapy and their likelihood of seeking out this form of therapy. MethodsIn total, 265 graduate students completed a cross-sectional web-based survey that included multiple-choice and open-ended questions assessing their perceptions of text-based therapy and the likelihood of seeking out this form of therapy. Chi-square tests, ANOVAs, and nonparametric Wilcoxon signed-rank tests were used to examine differences in multiple-choice questions. The constant comparative method was used for qualitative analyses of the open-ended question responses. ResultsParticipants (n=265) were predominately non-Hispanic White (166/265, 62.6%) and female (167/265, 63%) with a mean age of 28.3 (SD 5.1) years. Over half of the participants (139/265, 52.5%) were not aware that text-based therapy existed; however, 65.3% (173/265) reported that they would consider using text-based services, if available. In comparison to face-to-face therapy, participants reported being less likely to seek out text-based therapy and perceived it as less effective (P<.001). Qualitative results indicated that participants were concerned about the ability to effectively communicate and build rapport through text-based therapy and thought that this modality may be more effective for some mental and behavioral health concerns than others. Moreover, participants noted that text-based therapy would be best implemented as a way to supplement, rather than replace, face-to-face services. ConclusionsAltogether, the results of this study suggest that text-based therapy holds the potential to increase access to and use of mental and behavioral health services; however, graduate students remain concerned about its effectiveness and the optimal methods of implementation. Future research should investigate how therapeutic processes (eg, effective communication and rapport-building) can be facilitated in digital environments and how text-based therapy could be best implemented to supplement and extend, rather than replace, face-to-face services.